2022
DOI: 10.1515/gps-2022-0046
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus removal from aqueous solution by adsorption using wetland-based biochar: Batch experiment

Abstract: This article experiments wetland-based biochar as an effective adsorbent for phosphorus removal. In this experiment, four common wetland plants, canna (C), umbrella palm (U), bamboo reed (B), and Thalia dealbata (T), were used as the main raw materials. Twelve kinds of biochar (C300, C500, C700, U300, U500, U700, B300, B500, B700, T300, T500, and T700) were obtained at three pyrolysis temperatures (300°C, 500°C, and 700°C). The results show that canna (C) and umbrella palm (U) are more suitable as raw material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…If the plant residues are not treated in time, it will affect not only the ecological environment, but also waste resources. In our previous studies, we used four kinds of wetland plants (canna, umbrella palm, bamboo reed, and thalia dealbata) as raw materials to prepare biochar at different temperatures, and found that the biochar obtained at 700 • C was more conducive to P adsorption and that the maximum theoretical adsorption capacity of canna biochar was up to 39.24 mg/g [23]. In addition, canna is widely distributed in wetlands, its biomass is large, and the number of canna wetland plant residues has increased; therefore, canna biochar sources are widespread, their cost is low, and the use of canna biochar to remove P can not only solve the problem of water eutrophication, but also solve the problem of wetland plant solid waste residues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the plant residues are not treated in time, it will affect not only the ecological environment, but also waste resources. In our previous studies, we used four kinds of wetland plants (canna, umbrella palm, bamboo reed, and thalia dealbata) as raw materials to prepare biochar at different temperatures, and found that the biochar obtained at 700 • C was more conducive to P adsorption and that the maximum theoretical adsorption capacity of canna biochar was up to 39.24 mg/g [23]. In addition, canna is widely distributed in wetlands, its biomass is large, and the number of canna wetland plant residues has increased; therefore, canna biochar sources are widespread, their cost is low, and the use of canna biochar to remove P can not only solve the problem of water eutrophication, but also solve the problem of wetland plant solid waste residues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, canna is widely distributed in wetlands, its biomass is large, and the number of canna wetland plant residues has increased; therefore, canna biochar sources are widespread, their cost is low, and the use of canna biochar to remove P can not only solve the problem of water eutrophication, but also solve the problem of wetland plant solid waste residues. However, unmodified canna biochar has certain limitations in P removal, and there is a risk of P release in the treatment of wastewater containing P below 50 mg/L [23], because it is generally negatively charged and has a repulsive effect with phosphate. It has been reported that the adsorption capacity of the original oak BC produced at 550 • C is only 2.5 µmol/g, while the original corn BC cannot even adsorb any P [24,25].…”
Section: Introductionmentioning
confidence: 99%